2019
DOI: 10.1177/0018578719828335
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Fentanyl Use in Neonates

Abstract: Background: The recent addition of intranasal medication options for procedural sedation and analgesia has decreased the need for additional painful procedures such as intravenous lines for medication administration. Intranasal fentanyl (INF) has been used in the prehospital setting, as well as in the emergency department for several years, and is increasingly utilized in other locations such as the neonatal intensive care unit (NICU). A paucity of data exists in these smallest children, so we sought to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Sucrose was administered to all patients in conjunction with IN fentanyl in the study by McNair et al (13) and IN midazolam was administered concurrently with IN fentanyl in almost half of the 67 events in the study by Kaushal et al (14). No major adverse events were attributed to IN fentanyl use in the published studies (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Sucrose was administered to all patients in conjunction with IN fentanyl in the study by McNair et al (13) and IN midazolam was administered concurrently with IN fentanyl in almost half of the 67 events in the study by Kaushal et al (14). No major adverse events were attributed to IN fentanyl use in the published studies (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 94%
“…Four retrospective studies on the use of IN fentanyl in newborns and infants have been published thus far (12)(13)(14)(15) (Table 1). Except for the study by Harlos et al that prescribed IN fentanyl in the palliative care setting (12), the remaining studies evaluated its use for procedural pain in the NICU (13)(14)(15). The sample size in these studies ranged from 2 to 54 patients with mean/median gestational age (GA) at birth ranging from 26 to 35 weeks (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nasal drugs for procedural sedation and analgesia in neonates are increasing (51)(52)(53)(54)(55) and may be used as pre-medication before intubation of newborns. Milési et al compared intranasal midazolam and ketamine for neonatal intubation in pre-term neonates and found that the initial respiratory and hemodynamic tolerance of the two drugs were comparable despite 2-4 mg/kg nasal ketamine being less efficient than nasal midazolam in rapidly achieving adequate sedation for intubation (54).…”
Section: Pre-medicationmentioning
confidence: 99%